2017
DOI: 10.1111/jog.13481
|View full text |Cite
|
Sign up to set email alerts
|

Hypervascular retained product of conception: Characteristic magnetic resonance imaging and possible relationship to placental polyp and pseudoaneurysm

Abstract: The cases of two patients who developed myometrial vascularization following dilatation and curettage are described. In case 1, pathological diagnosis was possible with the resected specimens. This patient had hypervascular retained products of conception (RPOC). In case 2, the natural course of this pathological condition was observed, confirming a process of regression during repeated withdrawal bleeding. The three principal magnetic resonance imaging (MRI) findings in these cases were: (i) presence of a rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 7 publications
1
15
0
1
Order By: Relevance
“…In our study, MRI examinations were performed for patients with RPOC, CSP, and GTD. The ow void sign, such as multiple dotlike, tubular structures or multiple serpentine with low signal intensity on both T1WI and T2WI, could be found in patients with uterine AVMs in the myometrium and parametrium, which is consistent with the ndings of several previous studies [20,24,28,29,30,31] . Additionally, in clinical practice, we found that the ow void sign can also be observed in patients without uterine AVMs, and there was no signi cant difference between patients with and without AVMs (P > 0.05).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In our study, MRI examinations were performed for patients with RPOC, CSP, and GTD. The ow void sign, such as multiple dotlike, tubular structures or multiple serpentine with low signal intensity on both T1WI and T2WI, could be found in patients with uterine AVMs in the myometrium and parametrium, which is consistent with the ndings of several previous studies [20,24,28,29,30,31] . Additionally, in clinical practice, we found that the ow void sign can also be observed in patients without uterine AVMs, and there was no signi cant difference between patients with and without AVMs (P > 0.05).…”
Section: Discussionsupporting
confidence: 91%
“…As previously described [24,28,29,30,31] , the ow-void sign was de ned as multiple dotlike, tubular structures or multiple serpentine with low signal intensity located within the myometrium and parametrium on both T1WI and T2WI in our study.…”
Section: Image Analysismentioning
confidence: 62%
See 3 more Smart Citations